Constitution’s Supremacy Principle and Its Certain Characteristics - Chekhovych, T. V. (Кұқық және мемлекет, № 1 (106), Maqsut Narikbayev University, 2025)
The article is focused on analyzing certain elements of the Constitution’s supremacy principle. The author attempts to answer the question about the system of subjects to whom the mentioned principle is applied, as well as to distinguish it from rule of law and rule-of-law principle. Based on the results of studyung the first of these issues, it has been concluded that the Constitu- tion’s supremacy principle should be extended to absolutely all participants of public relations (subjects of public authority, politicians and private individuals). The state and society need a regulatory model of acceptable behavior that would unite everyone (private and public subjects) into a single system. The author has concluded that rule of law is focused on the fact that the most important public rela- tions related to constitutional rights, freedoms of a person and avcitizen, as well as the competence and powers of public authorities should be exclusively established by law (Act of Parliament). In terms of establishing the content of the Constitution’s supremacy principle, the author has noted that there is currently a problem of its practical application, since executive authorities cannot evade the requirements of laws and by-laws due to their unconstitutionality. The author of the article has suggested own solution to this problem. The last part of the article is focused on analyzing the content of the rule-of-law principle. According to the author, this principle is decisive, including for the Constitution. The «constitutionality» of the Constitution is ensured through the rule-of-law principle
Keywords: Constitution, Constitution’s supremacy principle, law, regulatory legal act, rule of law, rule-of-law principle, Constitutional Court, parliament, politicians, executive authorities